How Contract Farming Shapes Farmer Satisfaction: Evidence from Broiler Partnerships in Rural Indonesia - Annisa Miranti; Ma'ruf Tafsin; Iskandarini Iskandarini (Baileo: Jurnal Sosial Humaniora, 2026)
Contract farming has become an important institutional mechanism for integrating smallholder poultry farmers into modern agrifood value chains, yet little is known about how its service governance shapes farmer satisfaction beyond economic outcomes. This study examines how institutional service quality influences farmer satisfaction within broiler contract farming in rural Indonesia. A cross-sectional survey was conducted with 73 contract broiler farmers affiliated with seven partnership companies in Langkat Regency, North Sumatra. Data were collected using structured questionnaires covering sixteen partnership service attributes and analyzed through Importance–Performance Analysis (IPA) and the Customer Satisfaction Index (CSI). The findings indicate that farmers were generally satisfied with the partnership system (CSI = 68.60%), although a substantial gap remained between service performance and farmers’ expectations. Attributes associated with production risk management—including the quality of day-old chicks, veterinary inputs, technical assistance, harvest timeliness, and compensation—represented the highest priorities for improvement, whereas feed quality, feed pricing, production standards, and harvest price conformity constituted the system’s principal strengths. These findings demonstrate that farmer satisfaction is shaped not only by economic incentives but also by institutional service quality, governance responsiveness, and risk-sharing arrangements. The study advances the contract farming literature by framing partnership performance as an institutional governance issue and offers an evidence-based framework for strengthening sustainable, farmer-centered contract farming in rural agrifood systems.